Dissecting the components controlling root-to-shoot arsenic translocation in Arabidopsis thaliana - Wang, Chengcheng; Na, GunNam; Bermejo, Eduardo Sanchez; Chen, Yi; Banks, Jo Ann; Salt, David E.; Zhao, Fang-Jie (Wiley, 2017)
Arsenic (As) is an important environmental and food-chain toxin. We investigated the key components controlling As accumulation and tolerance in Arabidopsis thaliana. We tested the effects of different combinations of gene knockout, including arsenate reductase (HAC1), γ-glutamyl-cysteine synthetase (γ-ECS), phytochelatin synthase (PCS1) and phosphate effluxer (PHO1), and the heterologous expression of the As-hyperaccumulator Pteris vittata arsenite efflux (PvACR3), on As tolerance, accumulation, translocation and speciation in A. thaliana. Heterologous expression of PvACR3 markedly increased As tolerance and root-to-shoot As translocation in A. thaliana, with PvACR3 being localized to the plasma membrane. Combining PvACR3 expression with HAC1 mutation led to As hyperaccumulation in the shoots, whereas combining HAC1 and PHO1 mutation decreased As accumulation. Mutants of γ-ECS and PCS1 were hypersensitive to As and had higher root-to-shoot As translocation. Combining γ-ECS or PCS1 with HAC1 mutation did not alter As tolerance or accumulation beyond the levels observed in the single mutants. PvACR3 and HAC1 have large effects on root-to-shoot As translocation. Arsenic hyperaccumulation can be engineered in A. thaliana by knocking out the HAC1 gene and expressing PvACR3. PvACR3 and HAC1 also affect As tolerance, but not to the extent of γ-ECS and PCS1.